2001
DOI: 10.1002/pola.1154
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photochemical property of polymers with pendant donor–acceptor‐type norbornadiene moieties

Abstract: The donor-acceptor-type norbornadiene (D-A NBD) 1,4,5,6-tetramethyl-3phenyl-2,5-NBD-2-carboxylic acid was prepared by the Diels-Alder reaction of methyl 3-phenylprop-2-ynoate with 1,2,3,4-tetramethyl-1,3-cyclopentadiene. 1,4,5,6,7-Pentamethyl-3-phenyl-2,5-NBD-2-carboxylic acid was also synthesized in the same way. Styrene-type polymers with pendant D-A NBD moieties were prepared with a 100% degree of substitution (DS) by the reaction of D-A NBD carboxylic acids with poly[(p-chloromethyl)styrene] with 1,8-diaza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…In addition to conversion and storage of solar energy, the photochemical isomerization of NBD has been studied as a new alternative in the field of optoelectronics (memory, optical switches and other devices), as a photochromic system with potential application in the data storage technology, and as an energetic binder for solid rocket propellants . NBD structures are generally introduced into polymer chains as pendant moieties by postpolymerization chemical modification, by radical or cationic polymerizations of NBD‐containing vinyl monomers, or by ring‐opening copolymerization of glycidyl esters containing NBD moieties with various carboxylic anhydrides . Besides, the synthesis of polyamides containing NBD structure in the backbone by direct or catalyst transfer polycondensation has been reported earlier …”
Section: Introductionmentioning
confidence: 99%
“…In addition to conversion and storage of solar energy, the photochemical isomerization of NBD has been studied as a new alternative in the field of optoelectronics (memory, optical switches and other devices), as a photochromic system with potential application in the data storage technology, and as an energetic binder for solid rocket propellants . NBD structures are generally introduced into polymer chains as pendant moieties by postpolymerization chemical modification, by radical or cationic polymerizations of NBD‐containing vinyl monomers, or by ring‐opening copolymerization of glycidyl esters containing NBD moieties with various carboxylic anhydrides . Besides, the synthesis of polyamides containing NBD structure in the backbone by direct or catalyst transfer polycondensation has been reported earlier …”
Section: Introductionmentioning
confidence: 99%
“…The introduction of NBD groups into the polymer chains as a side groups were performed either by chemical polymer modification,14–18 by cationic polymerization of NBD containing vinylic monomers,19 or by ring‐opening copolymerization of glycidyl esters containing NBD moieties with carboxylic anhydrides 20…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Nishikubo et al [14][15][16][17] reported that polymers containing certain norbornadiene (NBD) moieties in the main and side chains showed high photochemical reactivity, and had a high photo-energy storage capability. NBD is converted to quadricyclane (QC) under UV irradiation, and the resulting polymers are expected to be good photo-energy transformation systems.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%